Progressive methods in data warehousing and business intelligence : concepts and competitive analytics - Taniar, David (Hershey, PA : Information Science Reference, 2009)
"This book observes state-of-the-art developments and research, as w ell as current innovative activities in data warehousing and mining, fo cusing on the intersection of data warehousing and business intelligenc e"--Provided by publisher.
"Premier reference source"--Cover.
Includes bibliographical references (p. 338-360) and index.
Keywords: Business intelligence -- Data processing; Data warehousing; Data mining